Analisis Penerapan Sistem Activity Based Costing (ABC) Dalam Menentukan Harga Pokok Produksi Pada UD. Sumber Rejeki - Aulia Khusai Ratul Ambia; Alfianti Wulan Wandari Valenza; Umar Alhadi; Afdilah Rivky Metahesya; Fakhri Rahman Azzura; Saridawati Saridawati (Pusat Riset dan Inovasi Nasional, 2024)
Manufacturing companies in determining the cost of production use the Activity Based Costing System (ABC) method as a more effective determinant of the cost of production for the company. This research aims to determine the cost of production of manufacturing companies at UD Sumber Rejeki. The data collection method is through descriptive research methods. The result of this research is that the cost of production using the Activity Based Costing System (ABC) method for office desks is obtained by a difference of Rp. 100,033 and Rp. 2,766,783 for bunk beds. Meanwhile, cupboards using the traditional method get a difference of IDR 500,000 compared to using the method Activity Based Costing System (ABC).